Contemporary periodization of altitude training for elite endurance athletes: A narrative review - Mujika, I.; Sharma, A. P.; Stellingwerff, T. (Sports Medicine, 2019)
Since the 1960s there has been an escalation in the purposeful utilization of altitude to enhance endurance athletic performance. This has been mirrored by a parallel intensification in research pursuits to elucidate hypoxia-induced adaptive mechanisms and substantiate optimal altitude protocols (e.g., hypoxic dose, duration, timing, and confounding factors such as training load periodization, health status, individual response, and nutritional considerations). The majority of the research and the field-based rationale for altitude has focused on hematological outcomes, where hypoxia causes an increased erythropoietic response resulting in augmented hemoglobin mass. Hypoxia-induced non-hematological adaptations, such as mitochondrial gene expression and enhanced muscle buffering capacity may also impact athletic performance, but research in elite endurance athletes is limited. However, despite significant scientific progress in our understanding of hypobaric hypoxia (natural altitude) and normobaric hypoxia (simulated altitude), elite endurance athletes and coaches still tend to be trailblazers at the coal face of cutting-edge altitude application to optimize individual performance, and they already implement novel altitude training interventions and progressive periodization and monitoring approaches. Published and field-based data strongly suggest that altitude training in elite endurance athletes should follow a long- and short-term periodized approach, integrating exercise training and recovery manipulation, performance peaking, adaptation monitoring, nutritional approaches, and the use of normobaric hypoxia in conjunction with terrestrial altitude. Future research should focus on the long-term effects of accumulated altitude training through repeated exposures, the interactions between altitude and other components of a periodized approach to elite athletic preparation, and the time course of non-hematological hypoxic adaptation and de-adaptation, and the potential differences in exercise-induced altitude adaptations between different modes of exercise.